POLA KUMAN DAN FAKTOR RISIKO PADA PASIEN ABSES LEHER DALAM DI RUMAH SAKIT ATMA JAYA - Kendrick Klaudius Hartedja; Ricky Yue; Lucky H. Moehario (Bahasa Indonesia, 2021)
Introduction: Deep neck abscess is a pus accumulation in the space and tissue of the cervical fascia caused by an infection and has the potential for several complications. Appropriate use of antibiotics can prevent these complications, but long culture time has been a main concern. Diabetes and oral hygiene are identified as commonly found risk factors for deep neck abscess. This study aims to analyze patients’ characteristics and the usage of antibiotics in treating deep neck abscess patients in Atma Jaya Hospital as well as assessing the effect of diabetes and oral hygiene as the causes for deep neck abscess. Methods: This was a cohort retrospective, descriptive analytic study. The samples were from 23 deep neck abscess patients undergoing treatment in Atma Jaya Hospital and met the inclusion and exclusion criteria. Chi square and Fisher exact test were used to determine the significance effect of diabetes and higiene oral in relation to deep neck abscess. Results: There were more male patients than female patients with age range 20-30 years old. Streptococcus viridans and Streptococcus pyogenes were the most common bacteria causing deep neck abscesses. Metronidazole, gentamicin and ceftriaxone were the most widely used antibiotics and it had shown great compatibility to fight against germs found in this disease. Statistical test results on the effect of oral hygiene oral to submandibular abscesses, peritonsillar, and Ludwig’s angina were p(AS)=0.605, p(AP)=1.000, and p(LA)=1.000, while of diabetes were p(AS)=0.685, p(AP)=0.657, and p(LA)=1.000. Conclusion: Deep neck abscess tends to occur in male patients of productive age. Metronidazole, gentamicin and ceftriaxone were the recommended empiric antibiotics. There was no significant relationship between oral hygiene and diabetes on the occurrence of deep neck abscesses.